Edukacja w szkole „etnicznej”: problemy i perspektywy (na przykładzie Czerniowiec, Ukraina) - Shestakova, Kateryna (Kraków: Wydawnictwo „Impuls”, 2010)
Experience and attainments o f intercultural communication influence on the level o f ethnic tolerance. Results o f the research conducted in Chernivtci, Ukraine, demonstrate that there is a correlation between the tolerance and ethnic stereotypes, on the one hand, and education in the “ethnic” school, on the other. In such type o f schools develops the area which can be explained in the terms “my”, “ours”, “cultural”, “safe”, “harmonize” etc. Ethnic minoritys school is very important channel o f the social identity for non-Ukrainian ethnic families. As a resuit we found out, that interethnic relations are very friendly in the Chernivtci region. At the same time our research indicated the negative tendencies in the interethnic relationships. It can happen from different reasons. Firstly, because of lack of modern strategies of ethnic minorities’ education. This kind o f strategies simultaneously has to assist in resolving of the social problems o f ethnic groups, in protecting of the human rights and in satisfying of the culturalneeds. Secondly, because of lack of well-prepared specialists on the questions of intercultural communication among the teachers.
Keywords: Interethnic relationships, education in the “ethnic” school